Information Technology Resources and Knowledge Management in Competitive Advantage with the Mediating Role of Organizational Commitment (Case Study: Tile and Ceramic Company) - Mostafa Chehr Azad (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Information technology resources and knowledge management in competitive advantages with mediating role of organizational commitment (case study: tile and ceramic company) has been examined in this study. The researcher tries to explain this issue in ceramic and tile companies using statistical analysis of data collected through the questionnaire as well as structural equation and SPSS and PLS software. The statistical society consisted of employers and managers at Tile and Ceramic Company and 96 subjects were selected as samples among them. In this study, the effect of information technology resources on knowledge creation, knowledge sharing, knowledge use, and knowledge saving with mediating role of organizational commitment on samples and finally the role of knowledge management on competitive advantages have been evaluated. According to the results of this study, some of the hypotheses are not significant; i.e., there is no significant and direct relationship between information technology resources and knowledge creation, knowledge sharing, knowledge use, and knowledge saving with mediating role of organizational commitment. Also, knowledge management affects the competitive advantage acquisition.